Can mirror visual feedback improve sensory relearning outcomes following median/ulnar nerve repair?. (2018) - Saberi, Farzaneh; Lajevardi, Laleh; Azad, Akram; Mirzaie, Leila; Taghizadeh, Ghorban; Abdolrazaghi, Hossein Ali
No abstract available